A pertographic and geochemical study of selected peridotitic and pyroxenitic xenoliths from the three kimberlite localities in the Lac de Gras region, Northwest Territories, Canada - Doyle, Patricia Mary (Department of Geological Sciences, 2016)
Includes bibliographical references.